Ruminal phytate degradation of maize grain and rapeseed meal in vitro and as affected by phytate content in donor animal diets and inorganic phosphorus in the buffer. Issue 5 (8th March 2016) - Haese, E.; Lengowski, M.; Gräter, E.; Föll, A.; Möhring, J.; Steingass, H.; Schollenberger, M.; Rodehutscord, M.
Summary: The ruminal disappearance of phytate phosphorus (InsP6 ‐P) from maize grain and rapeseed meal (RSM) was determined in two in vitro studies. In experiment 1, two diets differing in phosphorus (P) and InsP6 ‐P concentration were fed to the donor animals of rumen fluid (diet HP: 0.49% P in dry matter, diet LP: 0.29% P). Maize grain and RSM were incubated in a rumen fluid/saliva mixture for 3, 6, 12 and 24 h. In experiment 2, a diet similar to diet HP was fed, and the rumen fluid was mixed with artificial saliva containing 120 mg inorganic P/l (Pi) or no inorganic P (P0). Maize grain and RSM were incubated with either buffer for 3, 6, 12 and 24 h. Total P (tP) and InsP6 concentration were analysed in the fermenter fluids and feed residues. The disappearance of InsP6 ‐P from maize was completed after 12 h of incubation in both experiments. From RSM, 93% (diet LP) and 99% (diet HP) of the InsP6 ‐P in experiment 1 and 80% (Pi) and 89% (P0) in experiment 2 had disappeared after 24 h of incubation. InsP6 ‐P disappearance was higher when diet HP was fed (maize: 3 and 6 h; RSM: 6 and 24 h of incubation) and when rumen fluid was mixed with buffer P0 (maize: 6 h; RSM: 12 and 24 h of incubation). InsP6 ‐P concentration in the fermenter fluids was higher for maize, but no accumulation of InsP6 ‐P occurred, indicating a prompt degradation of soluble InsP6 . These results confirmed the capability of rumen micro‐organisms to efficiently degrade InsP6 . However, differences between the feedstuffs and diet composition as well as the presence of inorganic P in the in vitro system influenced the degradation process. Further studies are required to understand how these factors affect InsP6 degradation and their respective relevance in vivo .